EXPLORATION OF HUMANISTIC LEADERSHIP PRACTICES AMONG THE HEADS OF PRODUCTION UNITS IN THE TEXTILE INDUSTRY IN BEKASI CITY - Sumarsid, Sumarsid (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to explore humanistic leadership practices implemented by production unit heads in the textile industry in Bekasi City. The research approach used was qualitative, using in-depth interviews, observation, and internal document analysis. Data were analyzed using NVivo to obtain systematic and in-depth findings. The results showed that production unit heads with medium to high experience and at least a high school or diploma education were able to implement humanistic practices consistently. These practices encompassed pre-shift briefings, burden modifications, non-material incentives, and individual consultations, all of which fostered enhanced motivation, job satisfaction, and interpersonal relationships among employees. Supporting factors for humanistic practices encompassed the unit head's expertise, management endorsement, and a collaborative work environment, whereas obstacles were identified as production target pressures and resource limitations. The impact of humanistic practices was seen in increased productivity, operational stability, and worker well-being. This study highlighted the significance of including unit head attributes, leadership methodologies, and organizational support in fostering a productive and compassionate workplace. These findings are anticipated to provide a framework for the advancement of humanistic leadership approaches within the manufacturing industry.